Web application: Contribute to environment conservation - Pralhad R Gavali; Vrushabh Kupwade; Mayuri Kulkarni; Sumit Vajarinkar (Global Journal of Ecology - Peertechz Publications, 2021)
This website application will automate the major web operations. Everyone busy in their lives that they are finding convenient way to our refreshment, our comfort-zone that's way there is need to contribute for the Environment Conservation. The software product to be produced is a website application which will automate the major web operations. So we create such website application which helpful to user's for contribute for the conservation.  The purpose of this paper is to contribute for the environment with efficient way that could influence online user's perceptions and their behaviors, in order to achieve a successful website application. The main motive is to all users have to be more collaborative for this website. This is open for all and everyone can use it, no one is the owner, no one is a worker, everyone is a contributor for this collaboration.